A Multicenter Phase II Rater-Blinded Randomized Controlled Trial to Compare the Effectiveness of Eye Movement Desensitization Reprocessing Therapy vs. Treatment as Usual in Patients With Substance Use Disorder and History of Psychological Trauma: A Study Design and Protocol - Valiente-Gómez, Alicia; Moreno-Alcázar, Ana; Radua, Joaquim; Hogg, Bridget; Blanco, Laura; Lupo, W.; Pérez, Víctor; Robles-Martínez, Maria; Torrens, Marta; Amann, Benedikt L. (Frontiers in Psychiatry, 2019)
Background: Psychological trauma has a strong negative impact on the onset, course and prognosis of substance use disorders (SUD). Few trauma-oriented treatment approaches have been trialed, but preliminary evidence exists of the efficacy of Eye Movement Desensitization and Reprocessing (EMDR) therapy in improving clinical symptoms in SUD patients. Objective: To assess if EMDR therapy leads to 1) reduced substance consumption; 2) an improvement in psychopathological and in trauma-related symptoms; and 3) an improvement in overall functioning. Our hypothesis is that the EMDR group will improve in all variables when compared to the treatment as usual (TAU) group at 6 and 12-month visits. Method: In this single-blind randomized controlled trial (RCT), 132 SUD patients with a history of psychological trauma will be randomly assigned to EMDR (n=66) or to TAU (n=66). Patients in the EMDR group will receive 20 psychotherapeutic sessions of 60 minutes over 6 months. Substance use will be measured using the Timeline Followback Questionnaire, the Dependence Severity Scale and the Visual Analog Scale. Traumatic events will be measured by The Holmes-Rahe Life Stress Inventory, the Childhood Trauma Questionnaire Scale, the Global Assessment of Posttraumatic Stress Questionnaire, the Impact of Event Scale-Revised and the Dissociative Experiences Scale. Clinical symptomatology will be evaluated using the Hamilton Depression Rating Scale, the Young Mania Rating Scale and the Brief Psychiatric Rating Scale. Functionality will be assessed with the Functioning Assessment Short Test. All variables will be measured at baseline, post-treatment and 12 months as follow-up. Primary outcomes: a reduction in the degree of consumption of substances, an improvement in trauma-related symptoms, and in psychopathological symptoms. The secondary outcome: an improvement in overall functioning. Conclusion: This study will provide evidence of whether EMDR therapy is effective in reducing addiction-related, trauma and clinical symptoms and in improving functionality in patients with SUD and a history of trauma.